A corrupção no Brasil e a atuação do Ministério Público - Pimentel, Isabella Arruda (2014)
This study examines the occurrence of corruption in Brazil and the role of the State Public Prosecutor aiming at its combat, from 1988 to the present day (2014). The research conducted an investigation of the origin, formation and expressions of corruption in national public stage, beyond the historical reconstruction through theoretical and descriptive method. Aiming identify the mechanisms to combat corruption, was shown how the national democratic state based on rule of law is structured. It was pointed out the importance of citizenship as a powerful tool in fighting against this phenomenon. At the end of this demarche, the research analyzed the institution of the State Public Prosecutor and its performance fighting against corruption. Indeed, was shown that several paths can be traced to building an effective fight against this evil, so present in our societal context. Thus, this dissertation has the main objective to study the performance of the Brazilian State Public Prosecutor to fight against corruption and understand how this institution has worked and performed its prerogatives and functions effectively. Here, in brief, the nature, content and purpose of this research work.